Heritability and growth analysis of Brant`s oak (Quercus brantii Lindl.) based on sapling characteristics - Hossein Mirzaie-Nodoushan; Jafar Hosseinzadeh; Mehdi Pourhashemi; Shahin Mehrpur; Mojtaba Hamzehpour; Zahra Abravesh (تحقیقات جنگل و صنوبر ایران, 2018)
Brant`s oak (Quercus brantii Lindl.) is one of the most important tree species of Zagros forests. The major objective of the study was to assess various populations of the species for identification of plus tree individuals and growth trend analysis of the sapling of the selected trees. Therefore, seeds were collected from twelve single trees of one Brant`s oak populations located in Lorestan province. The selected trees were progeny tested based on a nested statistical design with three replications. Morphological data were biometrically and genetically analyzed, followed by investigating the trend of growth changes during the two years of the study. The selected trees were significantly different in the studied attributes. In addition, one of the progeny families showed outstanding domination over the others. Second year growth trend of 340 studied progeny saplings of the twelve families was similar to that of the first year. Meanwhile, the families with higher rank for the first-year growth based on seedling height, collar diameter and leaf number obtained better growth rates during the second year of the experiment. In other words, selecting plus trees based on progeny test at early years of sapling growth may effectively be used for selecting plus trees for breeding purposes such as seed orchard establishment. Furthermore, heritability of the studied characteristics varied between 0.48 to 0.99 and correlation coefficients between most of the paired characters increased for the second year.